Matematică
sofi312
8

A)x-6=(2-x)+[latex] \frac{1}{3} [/latex] b)2(x-3)+[latex] \frac{11}{4} [/latex]=x+[latex] \frac{3}{2} [/latex] c)(x-4)+x=[latex] \frac{1}{3} [/latex](x+2)-3 d)[latex] \frac{3}{8} [/latex](x+2)+=[latex] \frac{5}{6} [/latex](x-3)+2 e)0,(6)·(x+3)-0,(3)·(2x+1)=0,(5)·(x+2)

+0
(1) Răspunsuri
genius31

a)x-6=(2-x)+1/3 x+x=2+6+1/3 2x=8+1/3 2x=(8·3+1)/3 2x/1=25/3 2x·3=25 x=25/6=4,1(6) b)2(x-3)+=x+ 2x-6+11/4=x+3/2 2x-x=6-11/4+3/2 x=(6·4-11+3·2)/4 x=19/4 c)(x-4)+x=(x+2)-3 x-4+x=x/3+2/3-3 2x-x/3=4+2/3-3 (2x·3-x)/3=1+2/3 (6x-x)/3=(3+2)/3 5x=5 x=5/5 x=1 d)(x+2)+=(x-3)+2 3x/8+6/8+? e)0,(6)·(x+3)-0,(3)·(2x+1)=0,(5)·(x+2) 0,(6)=6/9=2/3 0,(3)=3/9=1/3 0,(5)=5/9 2/3(x+3)-1/3(2x+1)=5/9(x+2) 2x/3+6/3-2x/3-1/3=5x/9+10/9 2-1/3=5x/9+10/9 -5x/9=-2+1/3+10/9 -5x/9=(-2·9+3+10)/9 -5x/9=(-18+3+10)/9 -5x/9=(-15+10)/9 -5x/9=-5/9     (-1) 5x=5 x=5/5 x=1

Adaugă răspuns